2000
DOI: 10.1101/gr.152600
|View full text |Cite
|
Sign up to set email alerts
|

RIKEN Integrated Sequence Analysis (RISA) System---384-Format Sequencing Pipeline with 384 Multicapillary Sequencer

Abstract: The RIKEN high-throughput 384-format sequencing pipeline (RISA system) including a 384-multicapillary sequencer (the so-called RISA sequencer) was developed for the RIKEN mouse encyclopedia project. The RISA system consists of colony picking, template preparation, sequencing reaction, and the sequencing process. A novel high-throughput 384-format capillary sequencer system (RISA sequencer system) was developed for the sequencing process. This system consists of a 384-multicapillary auto sequencer (RISA sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 15 publications
0
32
0
Order By: Relevance
“…This analysis also revealed six potential sites of N-glycosylation (Asn-Xaa-Thr or Asn-Xaa-Ser) at positions 127, 175, 329, 424, 444, and 509. All of these structural features are also conserved in the amino acid sequence deduced from a mouse cDNA isolated as part of a large scale cDNA sequencing project (42). The protein encoded by this mouse cDNA (accession numbers AK004939 and BAB23684) likely corresponds to the mouse ortholog of the human serine proteinase identified in this work (Fig.…”
Section: Identification and Characterization Of A Human Fetal Liver Cmentioning
confidence: 63%
See 1 more Smart Citation
“…This analysis also revealed six potential sites of N-glycosylation (Asn-Xaa-Thr or Asn-Xaa-Ser) at positions 127, 175, 329, 424, 444, and 509. All of these structural features are also conserved in the amino acid sequence deduced from a mouse cDNA isolated as part of a large scale cDNA sequencing project (42). The protein encoded by this mouse cDNA (accession numbers AK004939 and BAB23684) likely corresponds to the mouse ortholog of the human serine proteinase identified in this work (Fig.…”
Section: Identification and Characterization Of A Human Fetal Liver Cmentioning
confidence: 63%
“…The amino acid sequence of human matriptase-2 identified in this work is shown in bold. The sequences for human and mouse matriptase were extracted from the SwissProt data base, whereas the sequence BAB23684 corresponding to the putative mouse matriptase-2 was deduced from a cDNA sequence reported in (42). The multiple alignment was performed with the PILEUP program of the GCG package.…”
Section: Production Of Recombinant Matriptase-2 In E Coli and Analysmentioning
confidence: 99%
“…Other glycopeptides from extracellular glycoproteins are commonly modified with high mannose oligosaccharides with between five and nine mannose residues in a distinct, microheterogeneic manner. In this study, two functionally unknown proteins were also identified, RIKEN cDNA 1100001H23 (44) and RIKEN cDNA 2310020A21 (45), as high mannose type oligosaccharide-carrying proteins. The N-glycosylation microheterogeneity analysis revealed that the former is modified with Man 5 GlcNAc 2 , Man 6 GlcNAc 2 , Man 7 GlcNAc 2 , and Man 8 GlcNAc 2 , whereas the latter is predominantly modified with M3 and M3F.…”
Section: Table I Observed Signals Of Aowr-labeled Oligosaccharides Rementioning
confidence: 99%
“…mRNA was prepared by standard methods (11). The cDNA synthesis was carried out by using a 25-g mRNA and first-strand cDNA primer (oligo dT [12][13][14][15][16][17][18] ) with SuperScript II RT in the presence of trehalose and sorbitol (13). Subsequently, full-length cDNA was selected with biotinylated cap-trapper Abbreviations: CAGE, cap analysis gene expression; TSP, transcriptional starting point; SAGE, serial analysis of gene expression; TU, transcriptional unit; RefSeq, Reference Sequence database.…”
mentioning
confidence: 99%